VD_FINDINFO Jug / 2016 / 285 vom 30. Juni 2015 - VD Tribunal cantonal (2015)
INDEMNITÉEN GÉNÉRAL, CIRCULATION ROUTIÈREDROIT DE LA CIRCULATION ROUTIÈRE, ADMISSION DE LA DEMANDE | 107 al. 2 LTF, 429 al. 1 let. a CPP (CH), 442 al. 4 CPP (CH)